2009
DOI: 10.1002/adfm.200801236
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effect of Nitrogen‐ and Oxygen‐Containing Functional Groups of Microporous Activated Carbon on its Electrochemical Performance in Supercapacitors

Abstract: Microporous activated carbon originating from coconut shell, as received or oxidized with nitric acid, is treated with melamine and urea and heated to 950 °C in an inert atmosphere to modify the carbon surface with nitrogen‐ and oxygen‐containing groups for a systematic investigation of their combined effect on electrochemical performance in 1 M H2SO4 supercapacitors. The chemistry of the samples is characterized using elemental analysis, Boehm titration, potentiometric titration, and X‐ray photoelectron spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
890
0
11

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,520 publications
(938 citation statements)
references
References 56 publications
19
890
0
11
Order By: Relevance
“…At low scan rates, NCh2 exhibits the highest capacity value, which agrees with the highest total content of nitrogen-and oxygen-containing functional groups on its surface, based on the XPS results ( Table 2). In addition, this sample possesses the highest content of pyridinic-N (N-6), pyrrolic/pyridonic-N (N-5), and quinone-O (O-I) groups, to whom the pseudocapacitive effect is attributed [33,34]. Hydroxyl groups were also found to contribute to pseudocapacitance [35].…”
Section: Electrochemical Performancementioning
confidence: 94%
“…At low scan rates, NCh2 exhibits the highest capacity value, which agrees with the highest total content of nitrogen-and oxygen-containing functional groups on its surface, based on the XPS results ( Table 2). In addition, this sample possesses the highest content of pyridinic-N (N-6), pyrrolic/pyridonic-N (N-5), and quinone-O (O-I) groups, to whom the pseudocapacitive effect is attributed [33,34]. Hydroxyl groups were also found to contribute to pseudocapacitance [35].…”
Section: Electrochemical Performancementioning
confidence: 94%
“…It has previously been reported that retaining some amount of oxygen moieties enhances the capacitive performance of graphene material in addition to the presence of nitrogen groups. 40 The partially reduced nature of our N-rGO ensures the presence of some residual oxygen functional groups which provide another pseudo-capacitive contribution to the total material capacitance. The capacitance per unit area reported here is approximately twice that reported previously using the same technique for nonfunctionalised liquid phase exfoliated graphene electrodes.…”
mentioning
confidence: 99%
“…A second peak is also present in each sample, centered around 531.5 eV, which may be attributed to oxygen double bonded to carbon as a quinone type group [23,51]. A very small third peak is seen at approximately 535.4 eV, which may correspond to chemisorbed oxygen or water [23,51]. After adding the hexamine coating to carbon, the relative amount of C−O as compared to C=O decreases.…”
Section: Science China Materialsmentioning
confidence: 99%
“…A summary of each of the different peaks and their percent contribution is shown in Table 3. The detailed scans of O1s peak show that each of the three samples has a peak centering at approximately 533.1 eV which can be attributed to oxygen single bonded to carbon in the form of phenol and/or ether groups [23,51]. A second peak is also present in each sample, centered around 531.5 eV, which may be attributed to oxygen double bonded to carbon as a quinone type group [23,51].…”
Section: Science China Materialsmentioning
confidence: 99%
See 1 more Smart Citation